Difference in allele frequency between sexes due to sex-specific dominance pattern - Czorlich, Yann; Aykanat, Tutku; Erkinaro, Jaakko; Orell, Panu; Primmer, Craig R. (Dryad Digital Repository, 2018)
Code associated with the article: Czorlich Y., Aykanat T., Erkinaro J., Orell P. & Primmer C.R. (2018) Rapid sex-specific evolution of age at maturity is shaped by genetic architecture in Atlantic salmon. Nature Ecology & Evolution. Simulations to determine how sex-specific dominance pattern may influence sex-specific allele frequency under selection.